Synthesis and Characterization of MgO–CuO–Fe2O3 Nanocomposite: A Study of Its Structural, Optical, and Antibacterial Properties - Adnan Alnehia; Annas Al-Sharabi; Hisham Alnahari; Muhammad Hadi (Journal of Chemistry)
The synthesis, characterization, and application of mixed oxide nanocomposites (NCs) are gaining recognition for their superior functional properties compared with simple metal oxides. In this study, we synthesized magnesium oxide (MgO)–copper oxide (CuO)–iron oxide (Fe2O3) mixed oxide NCs using a simple coprecipitation method and investigated several of their physical properties. X-ray diffraction (XRD) analyses revealed distinct phases, including monoclinic CuO, cubic MgO, cubic Fe2O3, and tetragonal CuFe2O4, with crystallite sizes ranging from 51 to 100 nm. Notably, the crystallite dimensions increased upon annealing at 800°C. UV-vis spectral analysis indicated two distinct energy bandgaps for the first sample at 3.10 eV and 4.18 eV and for the second sample at 3.44 eV and 2.67 eV, demonstrating a reduction in the optical energy bandgap with increasing temperature. Importantly, antibacterial assays revealed that the NCs exhibited a zone of inhibition of 24 mm against Gram-positive S. aureus; however, no significant antibacterial effect was observed against Gram-negative bacteria. These findings suggest that the MgO–CuO–Fe2O3 NC holds promise for healthcare and biotechnological applications, emphasizing the necessity for further exploration of its antibacterial properties for potential practical applications.